TEKNIK THINK FIND AND SAY BERBASIS MEDIA PUZZLE DALAM MENINGKATKAN KETERAMPILAN BERBICARA BAHASA PERANCIS - Agustina, Gina Sri Fitriani (2015)
The research discusses how the Think Find and Say technique with puzzle as its teaching medium can be used to enhance the students' French speaking proficiency. The research investigates: (1) the students' abilities in speaking French before and after implementing the Think Find and Say technique with puzzle as its teaching medium; (2) the function of the Think Find and Say technique with puzzle as its teaching medium to enhance the French speaking proficiency; and (3) the reaction of the students' to the Think Find and Say technique with puzzle as its teaching medium in enhancing their French speaking proficiency. This research employs pre-experiment method and utilizes one-group pre-test post-test design. The instruments of this research are literature review, test, and questionnaire. The data collection and data analysis display a significant difference before and after the Think Find and Say technique with puzzle as its teaching medium is implemented in French speaking class. Therefore, the hypothesis is accepted. The study concludes that the Think Find and Say technique with puzzle as its teaching medium is effective in enhancing the students' French speaking proficiency. Keywords: French speaking proficiency, teaching technique, the Think Find and Say technique with puzzle as its teaching medium Penelitian ini membahas mengenai teknik Think Find and Say berbasis media puzzle dalam meningkatkan keterampilan berbicara bahasa Perancis. Penelitian bertujuan untuk memperoleh informasi rinci mengenai: (1) tingkat kemampuan siswa dalam berbicara bahasa Perancis sebelum dan sesudah menggunakan teknik Think Find and Say berbasis media Puzzle; (2) teknik Think Find and Say berbasis media Puzzle dalam meningkatkan keterampilan berbicara bahasa Perancis; (3) tanggapan siswa terhadap teknik Think Find and Say berbasis media Puzzle dalam meningkatkan keterampilan berbicara bahasa Perancis. Metode penelitian yang digunakan di dalam penelitian ini adalah pra-eksperimen dengan disain one group pre-test post-test. Instrumen yang digunakan adalah studi pustaka, tes dan angket. Setelah mengumpulkan dan menganalisis data, diperoleh nilai rata-rata pre-test sebesar 15,3 dan nilai rata-rata post-test sebesar 20,05. Hal ini menunjukan adanya perbedaan hasil yang signifikan sebelum dan sesudah penggunaan teknik Think Find and Say dalam pembelajaran berbicara bahasa Perancis. Oleh karena itu, hipotesis kerja dapat diterima. Maka dapat disimpulkan bahwa penggunaan teknik Think Find and Say dianggap efektif dalam meningkatkan keterampilan berbicara bahasa Perancis siswa. Kata kunci: keterampilan berbicara, teknik pembelajaran, teknik Think Find and Say berbasis media puzzle